Pentingnya Memahami Soteriologi Paulus dan Yakobus - Erwin Tonius Zai (Badan Musyawarah Perguruan Tinggi Keagamaan Kristen Indonesia, 2020)
Salvation must be the most extensive subject in the Bibel. Salvation in the concept of the Apostles Paul dan James is very worthy of study considering that the two New Testament writers have given emphasis and description of salvation. In addition, the concept of salvation is a primary doctrine that is the dogmatic guide for the church. An understanding of salvation is always associated with these two New Testament writer's accounts. Paul emphasized that faith is the means to experience salvation. Meanwhile, James emphasizes work as the fruit of faith which is evidence of a person being saved. Hopefully, this article will contribute to the reader and answer the confusion over the misunderstanding of the concept of salvation between Paul and James.AbstrakKeselamatan harus menjadi pokok bahasan yang paling luas dalam Alkitab. Kese-lamatan dalam konsep Rasul Paulus dan Yakobus sangat layak untuk dikaji mengingat kedua penulis Perjanjian Baru ini telah memberikan penekanan serta gambaran tentang keselamatan. Selain itu konsep keselamatan merupakan doktrin primer yang menjadi pegangan dogmatika bagi gereja. Pemahaman tentang keselamatan selalu dihubungan dengan kedua catatan-catatan penulis Perjanjian Baru ini. Paulus menekankan iman yang menjadi sarana untuk mengalami keselamatan. Sedangkan Yakobus menekankan perbuatan sebagai buah dari iman yang adalah bukti dari orang yang sudah diselamatkan. Artikel ini semoga memberikan kontribusi kepada pembaca serta menjawab kebingunggan atas kekeliruan dalam memahami konsep keselamatan antara Paulus dan Yakobus.